Spectrum of pediatric urinary stone composition in North Western India: analysis at tertiary care center - Saran, Rama Kishan; Katti, Pawan; Mirdha, Kiran; Saran, Sanya; Takhar, Rajendra Prasad (International Journal of Research in Medical Sciences, 2019)
Background: Pediatric urolithiasis results in significant morbidity in later life. Incidence as well as site and chemical composition of calculi varies according to the changes in socio-economic conditions over time and the subsequent changes in dietary habits leading to a marked variation in the spectrum of urinary stone composition. To evaluate the spectrum of urinary stone composition in pediatric population from North-western India. Methods: This was a prospective observational study conducted between October 2013 and February 2019 which included pediatric patients with urolithiasis. Demographic and epidemiological characteristics including age, sex, geography, religion, socio-economic status, dietary habits were recorded. The location and sizes of stones were documented. The data was collected, analyzed and presented using summary statistics. Results: A total of 163 patients with urolithiasis were enrolled, of which 86 (53%) aged between 6 and 10 years, 49 (30%) aged between 11 and 14 years and 28 (17%) were aged between 0 and 5 years. The majority of patients were male (n=134; 82.21%). The most common location of the stone was urinary bladder (n=106; 65.03%) followed by kidney (n=33; 20.25%), urethra (n=16; 9.82%) and ureter (n=8; 4.91%). The upper tract (kidney and ureter) to the lower tract (bladder and urethra) stone ratio was 1:4. Stones with mixed composition were more than pure stones (73.62% versus 26.38%). The most common composition was the mixed stone of calcium oxalate, calcium phosphate and uric acid (n=36; 22.09%) followed by mixed stone of calcium oxalate monohydrate and dihydrate with uric acid (n=29; 17.79%), calcium oxalate and uric acid (n=25, 15.34%), calcium oxalate and calcium phosphate (n=20; 12.27%). Calcium oxalate was present in 80% of the stones, followed by uric acid in 7%, struvite in 6%, cystine in 3% and calcium phosphate in 2%. Conclusions: These results suggest that the prevalence of mixed stones with calcium oxalate as the predominant chemical component in the urinary stones of pediatric patients studied.